De Otra manera de ser: Entre lo público del espacio y la formación de una nueva ciudadanía democrática. (Una aproximación al interior de la alteridad como condición fundante de nuevas prácticas participativas) (REVISTA NODO, 2006)
On the last part of the 20th century, have been raise the concern of the public space that is a fundamental element for the human development. This issue has create new reflections that can generate theories and can move the discussion and the investigation with the most broad objective: find new concepts that can be formulate ideas that have not been yet explore in its study. Also it will help the argument to get the recognition as a way of social transformation and social renovation. This paper takes some reflections around the second phase of the investigation “heteronomy or approximations about the sense of public space, and its autonomy in this vital space” from the Institute of Projects and Investigations (INIP). The purpose of the second phase of the investigation is build up a theory base that will allow approach to analyze the complexity of the space and territory that can face the present problems of the Colombian cities.
Keywords: Public space; city; citizenship; education; new urbanism; participation; territoriality; territory